Salient Issues in Income and Asset Disclosure Systems : Lessons Learned from the Field in Preventing Conflict of Interest and Combating Illicit Enrichment - Burdescu, Ruxandra; Reid, Gary; Trapnell, Stephanie; Barnes, Dan; Kwapinski, Modest; Berger, Tammar (World Bank, Washington, DC, 2012)
Asset disclosure (AD) systems also referred to as financial disclosure or asset declarations can play two important roles within broader anticorruption efforts prevention and enforcement. On the prevention side, AD requirements can help bring to light conflict of interest risks faced by public officials who file ADs, thereby facilitating the avoidance of conflict of interest situations. On the enforcement side, AD requirements can provide one more source of information that may be used in the investigation and prosecution of suspected illicit enrichment cases, thereby aiding asset recovery efforts. Effective collaboration, both domestically and internationally, between policy makers and practitioners is essential for such benefits to materialize. In an effort to identify how best to design and implement an AD system, the report recognizes that each country ultimately must design a system that is tailored to the environment in which it will function. As such, the study analyzes some of the tradeoffs faced by policy makers and practitioners alike in designing and implementing an optimal AD system in a particular context. The report complements the Public Sector Governance Group's development of AGI, which include a set of indicators for both the legal framework and implementation of AD systems. These indicators are available to World Bank staff for monitoring and evaluating AD policies and procedures and for engaging in dialogue with client countries; they also are available to other interested parties outside the Bank.